Digital Marketing Strategy Public Relations Miracle Aesthetic Clinic Surabaya Via Instagram @miracle_surabaya: Strategi Digital Marketing Public Relations Miracle Aesthetic Clinic Surabaya Melalui Instagram @miracle_surabaya - Vincentius Jason Antaufhan; Santi Isnaini (Jurnal Media dan Komunikasi, 2023)
This study discusses the digital marketing strategy implemented by the Miracle beauty clinic in Surabaya. Miracle beauty clinic has Instagram as a digital-based marketing tool. Through the Instagram account @miracle_surabaya, Miracle shares various information, including: beauty products, exhibitions, beauty tips, and the responses of doctors from Miracle. This study was studied using content analysis through Instagram @miracle_surabaya by observing the contents uploaded by Miracle. The limitation of this research is the implementation area which is located in the city of Surabaya and the subject of discussion that examines the Public Relations strategy of Miracle Surabaya. The result of this research is that Miracle Aesthetic Clinic uses Instagram which is packed with warm content in order to be a pioneer of beauty clinics and to build the spirit of women with their respective beauty. Not only that, public relations plays an active role in maintaining image as well as building relationships with influencers as well as the public in order to achieve maximum results. Relationship building is carried out using social media, especially Instagram to be able to have an extraordinary and orderly impact.